1996
DOI: 10.3109/00048679609065044
|View full text |Cite
|
Sign up to set email alerts
|

The Psychiatric Care of People with Intellectual Disabilities: The Perceptions of Consultant Psychiatrists in Victoria

Abstract: Despite some positive findings, the majority of psychiatrists who responded held major concerns about the situation of people with intellectual disabilities. To improve the care provided to these people, it is recommended that these concerns are addressed by the psychiatric profession and responsible government departments in conjunction with university departments of psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 8 publications
3
86
1
1
Order By: Relevance
“…This desire for training parallels the findings of a recent Australian study (10), which reported that up to 76 percent of psychiatrists were interested in further training in how to treat psychiatric patients with developmental disabilities. Eighty-four percent of the respondents agreed or strongly agreed that specialized training in this field should be required during psychiatry residency.…”
Section: Discussionsupporting
confidence: 62%
“…This desire for training parallels the findings of a recent Australian study (10), which reported that up to 76 percent of psychiatrists were interested in further training in how to treat psychiatric patients with developmental disabilities. Eighty-four percent of the respondents agreed or strongly agreed that specialized training in this field should be required during psychiatry residency.…”
Section: Discussionsupporting
confidence: 62%
“…A study of Australian psychiatrists, for instance, found that 75% of those surveyed felt that they hadn't received sufficient training in dual diagnosis, and 39% preferred not to treat the dually diagnosed. 45 Since those with mild MR are less likely to have trouble communicating or severe baseline symptoms, the process of diagnosis is much less difficult for this group than for those with severe MR. 42 Consequently, individuals with mild MR may be more likely to be given a mental health diagnosis than those with more severe MR. It is unclear whether those with more severe MR are less likely to have such problems or merely less likely to be identified with mental health conditions.…”
Section: Risk For Mental Health Disorders Among Those With Mrmentioning
confidence: 99%
“…Research has also been conducted with medical students where although almost all students believed their future practice would include patients with developmental disabilities, 70% indicated that specialists in the area (and not themselves) should be providing primary care to this population (Burge et al, 2008). Over one third of surveyed Australian psychiatrists voiced that they would prefer not to serve individuals with a dual diagnosis of intellectual disability and mental health issues (Lennox & Chaplin, 1996). These findings are problematic to the health and well-being of those with developmental disabilities as decreased interest by professionals in working with the population may lead to clinicians who avoid taking on clients with developmental disabilities and to increased wait times for these patients to see specialists in the field.…”
mentioning
confidence: 87%
“…One important factor affecting the availability of services is the interest and attitudes of providers, as some health care providers have voiced a preference not to serve individuals with developmental disabilities (Edwards, Lennox, & White, 2007;Lennox & Chaplin, 1996) and would not choose a career in the area (Reinblatt, Rifkin, & Freeman, 2004). Within Canadian social work programs, a lack of faculty interest and expertise in developmental disabilities (Burge, Druick, Caron, Ouellette-Kuntz, & Paquette, 1999) and a lack of student interest in placements focused on developmental disabilities (Burge, Druick, Caron, & Ouellette-Kuntz, 1998) have been reported.…”
mentioning
confidence: 99%